ASSESSMENT OF THE IMMEDIATE AND REMOTE RESULTS OF EMBOLIZATION OF UTERINE ARTERIES AT PATIENTS WITH OBSTETRIC BLEEDINGS - Теленкова, Жанна Николаевна; Артымук, Наталья Владимировна; Васильковская, Елена Николаевна; Пешкова, Наталья Васильевна (Mother and Baby in Kuzbass, 2017)
Obstetrical hemorrhage (OH) is one of the leading causes of maternal death in the world. Study and implementation of organ-saving methods of OH treatment, one of wich is uterine artery embolization, is espessially important nowadays.The purpose – evaluation of immediate and long-term results of uterine artery embolization for patients with OH.Materials and methods. Prospective study were conducted on the basis of the maternity department of Khanty-Mansiysk's regional hospital. The observation conducted over 65 women with OH who undergo UAE from 2010 to 2016. The time of observation of patients varied between 6 months and 6 years. Inclusion criteria were: obstetric hemorrhage with a volume of ≥ 1000 ml, UAE. Exclusion criteria were: unstable hemodynamics, obstetric hemorrhage, severity wich required total hysterectomy. The immediate outcomes were estimated: the volume of blood loss before and during UAE, the duration of the intervention, the total volume of hemorrhage, the effectiveness of stopping obstetric hemorrhage, red blood (hemoglobin, hematocrit, erythrocyte), platelets, coagulogram after UAE on the first day, frequency and volume of blood transfusion, plasma-transfusion, the duration of inpatient treatment, the presence of complications. Long-term results of UAE were estimated as well: normal menstrual function recovery, fertility, outcomes of subsequent pregnancies. All of the patients were of reproductive age. 32 of them delivered vaginally while 33 delivered via cesarean section. The volume of blood loss before UAE (Me) was 1150 ml. Time gap between arriving at a decision to do UAE and carrying out the operation (Me) was 20 min. The average duration of an UAE (Me) was 31 min.Results. The additional blood loss during an UAE(Me) was 150 ml and the total volume of the blood loss (Me) reached 1300 ml. 98,5 % of the group had the bleeding fully stopped. In 90,8 % of the women, the postpartum period was without complications, they were discharged in a satisfactory condition. The average bed-day (Me) of treatment was 5 days (4 to 7 days). 9,2 % of the women had complications: hematometra 4,6 %, recurrent bleeding 1,5 %, necrosis of the uterus 3,1 %. In the long-term period almost all of the women (96,9 %) had their normal menstrual function back. 6 patients use IUD for contraception. 18,5 % (8,9-28,1 %) of the group conceived spontaneously on average in 3 years (2-4 years) after UAE. In the structure of the outcomes of the pregnancies that occurred 58,3 % completed with childbirth, 25 % with voluntary interruption, 16,7 % were undeveloped pregnancies.Conclusion. On the basis of the study it was revealed that UAE is a sufficiently effective organ-saving method of OH treatment. Menses are recovered and fertility is preserved after UAE.
Keywords: obstetrical hemorrhage; uterine artery embolization